Estudo dos marcadores de virulência tnpA, tnpB, cagM do helicobacter pylori e sua associação com afecções gástricas em Fortaleza, Brasil - Sousa, Ederson Laurindo Holanda de (2016)
Helicobacter pylori is a Gram-negative bacterium that colonizes more than half the world's population; Infection by this bacterium is associated with various gastric diseases, including: gastritis, peptic ulcers and gastric cancer. The degree of injury and pathogenicity is very dependent on the genetic diversity of the bacterium. The aim of this study was to evaluate the virulence factors tnpA, tnpB and H. pylori cagM in patients with gastritis, peptic ulcer and gastric cancer. Genotyping of H. pylori strains arising from gastric biopsies was performed by reaction using polymerase chain. 147 patients were analyzed, of which 50 had gastritis, 51 peptic ulcers and 46 gastric cancer; which 72 were male and 75 female, mean age and standard deviation of 54.18 ± 14.24 years. The study population was divided into two age groups below and above 45 years; which 72.8% were above 45 years of age. The frequency of genotypes was: 70 (47.6%) tnpA strains; 03 (2.0%) tnpB; 19 (12.9%) cagM. The tnpA gene was more prevalent in males in both age groups; however, no statistical association of the gene with such variables. The tnpA gene showed a negative association with gastric cancer; while significantly associated with duodenal ulcer (p = 0.002). The tnpB gene had the lowest prevalence and got no significant association. The cagM gene was the most prevalent second and showed a significant association with duodenal ulcer (p = 0.024). It was concluded that the tnpA genes, cagM are correlated with increased risk of developing peptic ulcers; suggesting that these genes are good candidates for genetic markers of H. pylori in peptic ulcer disease in these patients Fortaleza.